2011
DOI: 10.1002/maco.200905399
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behavior of polypyrrole/hydroxyapatite nanocomposite thin films electropolymerized on NiTi substrates in simulated body fluid

Abstract: Hydroxyapatite (HAp) nanoparticles synthesized via microwave irradiation. Polypyrrole (PPy)/HAp nanocomposite was obtained using electropolymerization on nitinol (Ni) titanium (Ti) substrates. Fourier transform infrared was employed to characterize the nanocomposite formation. Electrochemical properties of the nanocomposite were investigated using polarization and electrochemical impedance spectroscopy (EIS) in simulated body fluid (SBF, 37 AE 0.1 8C). It was concluded that the NiTi specimen coated with PPy/HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…It has the advantages of simplicity, reproducibility, low cost, and ease of producing (even in bulk quantities) of nanostructured materials [9,10]. The outstanding biological potentials of nanostructured biomaterials, which have not been observed in the conventional polycrystalline coarse grained materials, have been reported by previous studies [11][12][13].…”
Section: Introductionmentioning
confidence: 96%
“…It has the advantages of simplicity, reproducibility, low cost, and ease of producing (even in bulk quantities) of nanostructured materials [9,10]. The outstanding biological potentials of nanostructured biomaterials, which have not been observed in the conventional polycrystalline coarse grained materials, have been reported by previous studies [11][12][13].…”
Section: Introductionmentioning
confidence: 96%
“…2 Research efforts have been directed to the elimination of Ni release from the surface and therefore improving the corrosion resistance and as well as the biocompatibility of the implants. [1][2][3][4][5] Nickel is known for its diverse effects on human body, including allergic reactions and toxicity. 6 Studies on commercially available orthodontic wires showed increased Ni release rate with time of exposure and type of solution, indicating the need for better understanding the processes at the interface between the implant and biological environment.…”
Section: Introductionmentioning
confidence: 99%
“…2,7 Various surface modification techniques have been used including mechanical, chemical and thermal treatments, as well as bioactive coatings such as calcium phosphate coatings. 4,5,8,9 Hydroxyapatite coatings (HAP) are appropriate candidates for biocompatibility improvement since they offer an excellent surface for cell growth. 8,10 However, they cannot be used in load-bearing applications due to their poor mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…shape memory effect, superelasticity and high damping capacity [1][2][3][4]. As a metal material for medical implant, it should be resistant to corrosion to ensure long service life and to minimize its adverse biologic effect.…”
Section: Introductionmentioning
confidence: 99%
“…Polypyrrole (PPy) is particularly attractive due to its high conductivity, stability, ease of synthesis and especially very good tissue compatibility [2,10,16]. Moreover, PPy coating can be electrodeposited directly on the alloy surface easily [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%